Can LigaSure™ be used to perform sleeve gastrectomy? – Tensile strength and histological changes. Issue 3 (June 2014) - Lopez, Julio; Vilallonga, Ramon; Targarona, Eduardo M.; Balague, Carmen; Enriquez, Lenin; Rivera, Ramon; Balibrea, Jose M.; Perez-Ochoa, Francisco; Rodriguez, Karime; Baeza, Miguel; Reyes, Arturo
Abstract Introduction: LigaSure™ was developed as an alternative to suture ligatures, hemoclips and staplers for ligating vessels and tissue bundles. The aim of the present study was to determine whether LigaSure can be used as a welding instrument in the performance of laparoscopic sleeve gastrectomy. Material and methods: Gastric specimens were assigned into four groups. Group 1 - specimens remained with the staple line intact. Group 2 - the staple line was oversewn. Group 3 - the staple line was resected with LigaSure. Group 4 - staple line was resected with LigaSure and the seal was oversewn. In all specimens the pressure tolerance was assessed using a portable sensor. Results: In group 1 the leak pressure was 34.7 ± 11.7 whereas in group 2 specimens the pressure increased three-fold (101.9 ± 21.4). The LigaSure seal alone (group 3) achieved a mean pressure of 13.7 mmHg. However, in group 4 there was an exponential increase on their burst strength up to 142 mmHg (p = 0.0005). Conclusion: According to our results, LigaSure could be used to perform laparoscopic sleeve gastrectomy with reduction of staple-line bleeding and, when reinforced with a running suture, it achieves a strength that approaches that of staples plus oversewing.